2019
DOI: 10.1111/jgs.15940
|View full text |Cite
|
Sign up to set email alerts
|

The Montreal Cognitive Assessment After Omission of Hearing‐Dependent Subtests: Psychometrics and Clinical Recommendations

Abstract: Objectives Hearing loss (HL) is the third most common chronic health condition in older adults, yet it is often undiagnosed and/or untreated. Given the association between HL and cognitive impairment, it is expected that many people undergoing cognitive screening may have HL. The Montreal Cognitive Assessment (MoCA) is a brief screening test that assesses a wide range of cognitive functions sensitive to Alzheimer's disease (AD) and mild cognitive impairment (MCI). Although MoCA items were carefully designed to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 22 publications
0
37
0
Order By: Relevance
“…Because listening with auditory impairment is effortful, older adults with hearing loss may perform worse on these auditorybased cognitive assessments because more cognitive resources are directed towards listening, leaving fewer resources available for the cognitive processing required to perform adequately. The hearing-dependant subtests within tests of cognitive function may significantly affect their sensitivity and specificity as a screening tool [82]. Research shows that omitting the hearing-dependant subtests in one example of these cognitive tests (the Montreal cognitive assessment) reduces the sensitivity in diagnosing mild cognitive impairment; this points at the potential consequences of testing individuals with untreated hearing loss, or testing in a noisy environment, on the accuracy of the these cognitive screening measures [82].…”
Section: Concluding Remarks and Future Perspectivesmentioning
confidence: 99%
“…Because listening with auditory impairment is effortful, older adults with hearing loss may perform worse on these auditorybased cognitive assessments because more cognitive resources are directed towards listening, leaving fewer resources available for the cognitive processing required to perform adequately. The hearing-dependant subtests within tests of cognitive function may significantly affect their sensitivity and specificity as a screening tool [82]. Research shows that omitting the hearing-dependant subtests in one example of these cognitive tests (the Montreal cognitive assessment) reduces the sensitivity in diagnosing mild cognitive impairment; this points at the potential consequences of testing individuals with untreated hearing loss, or testing in a noisy environment, on the accuracy of the these cognitive screening measures [82].…”
Section: Concluding Remarks and Future Perspectivesmentioning
confidence: 99%
“…Though it is important to note that HI individuals underperform on the delayed recall task, removing these test items may decrease test sensitivity. 20 This is especially important given that performance on the delayed recall task is the most predictive of MCI or dementia. 21 A second suggestion has been to amplify test material during administration.…”
Section: And the Montreal Cognitive Assessmentmentioning
confidence: 99%
“…Hillyer et al showed similar results in participants with cochlear implants (CIs). Though it is important to note that HI individuals underperform on the delayed recall task, removing these test items may decrease test sensitivity . This is especially important given that performance on the delayed recall task is the most predictive of MCI or dementia …”
Section: Introductionmentioning
confidence: 99%
“…In contrast, sensitivity to detect AD was still between 87% and 100% in comparison to 100% in the original version. 70 Assessment tools that are fully independent of verbal instructions or responses such as the Raven`s Progressive Matrices, which is commonly used for the evaluation of the general intelligence 71 may be another choice. It`s usability as a non-verbal and language-independent test instrument has been proven.…”
Section: Cognitive Assessment Tools For Subjects With Sensory Impairmentmentioning
confidence: 99%